The Nexus of the Dark Triad Personality Traits With Cyberbullying, Empathy, and Emotional Intelligence: A Structural-Equation Modeling Approach - Schade, Estelle C.; Voracek, Martin; Tran, Ulrich S. (Frontiers in Psychology, 2021)
This study set out to elucidate the complex suite of associations between the Dark Triad personality traits (Machiavellianism, narcissism, and psychopathy), emotional intelligence, empathy, and cyberbullying, as the respective findings regarding this topic have been inconsistent. Studies preponderantly have relied on abbreviated Dark Triad measures that do not differentiate between its lower-order facets. Further, most extant studies have exclusively been based on female psychology undergraduates and have not accounted for known sex differences on the Dark Triad traits and cyberbullying, or for negative associations between cyberbullying and age. Therefore, this nexus of interrelations was investigated in a diverse community sample (N = 749). A structural equation-modeling approached was used to examine predictors of cyberbullying and to test for mediating relationships between lower-order Dark Triad facets and emotional intelligence and empathy. Multigroup models were applied to test for sex-specific patterns. Empathy did not predict cyberbullying, whereas emotional intelligence partly mediated the Dark Triad associations with cyberbullying among both sexes. Sex-specific patterns in the associations between Dark Triad traits and cyberbullying were particularly observed for the grandiose and vulnerable narcissism facets. Emotional intelligence appeared to buffer effects of grandiose narcissism on cyberbullying. Future research could fruitfully explore cyberbullies’ profiles regarding primary and secondary psychopathy, sex differences in narcissism, and buffering effects of emotional intelligence. Further improvements regarding the measurement of dark personality traits are indicated as well.